Social and emotional self-efficacy of adolescents: measured and analysed interdependencies within and across academic achievement level. Issue 3 (2nd July 2016) - Armum, Puspalathaa; Chellappan, Kalaivani
Abstract: The aim of the study was to measure self-efficacy of the adolescents from different academic achievement levels in Malaysia. A sample of 169 students was selected from different academic settings of Malaysia. Social and emotional self-efficacy of the adolescents comprises 16 items, adapted from the Self-Efficacy Questionnaire for Children to assess the social and emotional self-efficacy of children. Data of the research were analysed through descriptive and inferential statistics. The data analysis indicated that there is a significant difference in emotional self-efficacy across academic ability. However, there is no significant difference in social self-efficacy across academic ability among adolescents. Furthermore, the research showed that there is no significant difference in social and emotional self-efficacy across gender. The study recommends the findings of the study to be used as a guideline in developing a psychological instrument in assessing social and emotional self- efficacy of the adolescents in Malaysian context.